2006
DOI: 10.1091/mbc.e05-10-0980
|View full text |Cite
|
Sign up to set email alerts
|

Arf6-independent GPI-anchored Protein-enriched Early Endosomal Compartments Fuse with Sorting Endosomes via a Rab5/Phosphatidylinositol-3′-Kinase–dependent Machinery

Abstract: In the process of internalization of molecules from the extracellular milieu, a cell uses multiple endocytic pathways, consequently generating different endocytic vesicles. These primary endocytic vesicles are targeted to specific destinations inside the cell. Here, we show that GPI-anchored proteins are internalized by an Arf6-independent mechanism into GPI-anchored protein-enriched early endosomal compartments (GEECs). Internalized GPI-anchored proteins and the fluid phase are first visualized in GEECs that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
118
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 106 publications
(126 citation statements)
references
References 79 publications
(156 reference statements)
7
118
0
1
Order By: Relevance
“…Cells were then fixed and co-stained with EEA1 to assess whether CD59 reached early endosomes. As we and others have previously shown (41,42) antibody-bound internalized CD59 was predominantly found in early endosomes, as judged by its significant co-localization with endogenous EEA1 (Fig. 10A, pink structures in inset, quantified in C).…”
Section: Co-localization Of Internalized Rilyd4 With Cd59-containingsupporting
confidence: 82%
“…Cells were then fixed and co-stained with EEA1 to assess whether CD59 reached early endosomes. As we and others have previously shown (41,42) antibody-bound internalized CD59 was predominantly found in early endosomes, as judged by its significant co-localization with endogenous EEA1 (Fig. 10A, pink structures in inset, quantified in C).…”
Section: Co-localization Of Internalized Rilyd4 With Cd59-containingsupporting
confidence: 82%
“…Typically, vesicles derived from distinct endocytic pathways are initially observed as separate endosomes carrying characteristic cargoes. Subsequently, the vesicles undergo heterotypic fusion and mature into Rab5 + -sorting endosomes, from where cargoes can either be recycled or degraded (27). The merged early endosomes containing Wg and DFz2 (10-15 min) in the wing disc are also positive for Rab5 GFP (Fig.…”
Section: Resultsmentioning
confidence: 91%
“…We have previously shown that the fusion of the CG and CD pathway endosomes depend on Rab5 and a Wortmanin-sensitive class III PI3K (27) PI3K-Vps34 using C5GAL4 leads to defects in fusion of Wg and DFz2 endosomes (Fig. S7 A and B) and reduction in Wg signaling (Fig.…”
Section: Endocytosis and Endosomal Acidification Is Necessary For Winmentioning
confidence: 92%
“…From the early endosomes, molecules are either sorted for recycling or directed to late endosomes that are Rab7 and LAMP1 positive. Endosomes carrying cargo internalized via clathrin-independent pathways also fuse with Rab5-positive early endosomes (71,72). Studies with Dengue virus have demonstrated that the virus moves from Rab5-positive early endosomes to Rab7-positive late endosomes before viral RNA is released in the cytoplasm (11,12).…”
Section: Jev Internalization Is Dynamin-2 Dependentmentioning
confidence: 99%